Adhesive sheet and dicing die-bond film

JP2025024948APending Publication Date: 2025-02-21NITTO DENKO CORP

Patent Information

Application Number
JP2023129350
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、熱膨張性微小球を含む粘着剤層を含みつつも、平滑性に優れる粘着剤層を形成し得、かつ、被着体のエキスパンド性を阻害し難い粘着シートを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024948000001_ABST
    Figure 2025024948000001_ABST
Patent Text Reader

Abstract

To provide an adhesive sheet containing an adhesive layer with thermally expandable microspheres, while being capable of forming a highly smooth adhesive layer and less likely to hinder the expandability of the adherend.SOLUTION: According to an embodiment, an adhesive sheet comprises a substrate, a resin layer, and an adhesive layer in this order, where the adhesive layer comprises thermally expandable microspheres, the resin layer comprises a base polymer, and the base polymer has a glass transition temperature Tg of -35°C to 20°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet, and more particularly to a pressure-sensitive adhesive sheet capable of exhibiting easy peelability in response to a thermal stimulus. [Background technology]

[0002] Conventionally, adhesive sheets have been used to fix or temporarily fix workpieces when processing electronic components, etc. For example, during the manufacture of semiconductor chips, adhesive sheets are sometimes used as temporary fixing materials in an expanding process in which a semiconductor wafer provided with a weak spot by stealth dicing or the like is cleaved together with a die attachment film to widen the gap between adjacent semiconductor chips. Adhesive sheets used in such processes are required to have smooth adhesive surfaces and not to impair the expandability of the semiconductor wafer (chip) and the die attachment film. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-201452 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and an object of the present invention is to provide a pressure-sensitive adhesive sheet which, while including a pressure-sensitive adhesive layer containing heat-expandable microspheres, is capable of forming a pressure-sensitive adhesive layer having excellent smoothness and which is unlikely to inhibit the expandability of an adherend. [Means for solving the problem]

[0005] [1] An adhesive sheet according to an embodiment of the present invention comprises a substrate, a resin layer, and an adhesive layer, in this order. The adhesive layer contains heat-expandable microspheres. The resin layer has a base polymer, and the glass transition temperature Tg of the base polymer is in the range of −35° C. to 20° C. [2] In the pressure-sensitive adhesive sheet according to the above [1], the resin layer may have a loss modulus E'' at -15°C of 10 MPa to 3000 MPa. [3] In the pressure-sensitive adhesive sheet according to the above [1] or [2], the resin layer may have a storage modulus E' at -15°C of 10 MPa to 2500 MPa. [4] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [3], the resin layer may not be curable by active energy rays. [5] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [4], the resin layer may have a thickness of 5 μm to 40 μm. [6] In the pressure-sensitive adhesive sheet according to any one of [1] to [5] above, the base polymer may have a structural unit (A1) derived from a monomer (A1) having a glass transition temperature Tg of -20°C to 15°C when made into a homopolymer, and the content of the structural unit (A1) may be 50 parts by weight or more per 100 parts by weight of the base polymer. [7] In the pressure-sensitive adhesive sheet according to [6] above, the base polymer may be an acrylic polymer, and the monomer (A1) may be ethyl acrylate, methyl acrylate, or 2-ethylhexyl methacrylate. [8] In the pressure-sensitive adhesive sheet according to any one of [1] to [7] above, the base polymer may have a structural unit (B1) derived from a monomer (B1) having a glass transition temperature Tg of 100°C to 175°C when made into a homopolymer, and the content of the structural unit (B1) may be 40 parts by weight or less per 100 parts by weight of the base polymer. [9] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [8], the monomer (B1) may be methyl methacrylate, N-acryloylmorpholine, N-vinyl-2-pyrrolidone or N-phenylmaleimide.

[10] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [9], the pressure-sensitive adhesive layer may have a thickness of 5 μm to 40 μm.

[11] In the pressure-sensitive adhesive sheet according to any one of the above [1] to

[10] , the pressure-sensitive adhesive layer may have a light absorptance of 25% to 100% at a wavelength of 900 nm.

[12] In the pressure-sensitive adhesive sheet according to any one of the above [1] to

[11] , the substrate may contain a polyolefin resin.

[13] In the pressure-sensitive adhesive sheet according to any one of [1] to

[12] above, the substrate may include a layer formed from a polyolefin resin layer and a layer formed from an ethylene-vinyl acetate copolymer resin.

[14] A dicing die-bonding film according to an embodiment of the present invention comprises an adhesive sheet according to any one of [1] to

[13] above, and a die attach film. Effect of the Invention

[0006] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet which, while including a pressure-sensitive adhesive layer containing heat-expandable microspheres, can form a pressure-sensitive adhesive layer having excellent smoothness and which is unlikely to inhibit the expandability of an adherend. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of a dicing die-bonding film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] A. Overview of adhesive sheets 1 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. The pressure-sensitive adhesive sheet 100 comprises, in this order, a substrate 10, a resin layer 20, and a pressure-sensitive adhesive layer 30. The pressure-sensitive adhesive layer contains heat-expandable microspheres. As long as the effects of the present invention are obtained, the pressure-sensitive adhesive sheet may comprise any other appropriate layers. For example, another pressure-sensitive adhesive layer may be provided on the opposite side of the substrate to the stress transfer layer.

[0009] The heat-expandable microspheres can be foamed at a predetermined temperature. When the heat-expandable microspheres are foamed by heating, the adhesive layer containing such heat-expandable microspheres generates unevenness on the adhesive surface (i.e., the surface of the adhesive layer), and the adhesive strength is reduced or lost. When the adhesive sheet of the present invention is used as a sheet for temporarily fixing a workpiece during processing of electronic parts (e.g., semiconductor chips), the adhesive strength required for temporary fixing is exhibited when the workpiece is subjected to a predetermined processing (e.g., expanding the adherend, etc.), and when the workpiece is peeled off after processing, the adhesive strength is reduced or lost by heating, and good peelability is exhibited. Examples of the heating include heating by increasing the environmental temperature and heating by absorbing laser light into the adhesive layer.

[0010] In recent years, the ratio of functional layers to semiconductor chips has increased with the miniaturization and thinning of semiconductor packages, and as a result, semiconductor chips have tended to become fragile. When a conventional curable adhesive sheet is used for temporarily fixing such semiconductor chips, the semiconductor chips are likely to break when peeled off. On the other hand, the adhesive sheet having an adhesive layer containing thermally expandable microspheres exhibits releasability as described above, and is therefore useful for temporarily fixing fragile semiconductor chips. By using the adhesive sheet, the semiconductor chips can be peeled off without being broken.

[0011] The resin layer includes a base polymer, and the glass transition temperature Tg of the base polymer is −35° C. to 20° C. Such a resin layer can be a stress transfer layer that can preferably transfer stress to an adherend (e.g., a semiconductor chip / die attachment film laminate) when stretched in a state in which the adherend is attached (i.e., during expansion). The pressure-sensitive adhesive sheet can be preferably used as a temporary fixing material in an expanding step in which a semiconductor wafer having a weak spot provided by stealth dicing or the like is cleaved together with a die attachment film to widen the gap between adjacent semiconductor chips during the manufacturing of semiconductor chips. In an embodiment of the present invention, by providing the resin layer, even if the thickness of the pressure-sensitive adhesive layer is increased, stress relaxation of the pressure-sensitive adhesive sheet during expansion can be suppressed, and the adherend can be sufficiently stretched. Therefore, by using the pressure-sensitive adhesive sheet in the expanding step during the manufacturing of semiconductor chips, the semiconductor wafer can be preferably cleaved, and further, as described above, the semiconductor chip obtained by cleavage can be preferably peeled off by the action of the heat-expandable microspheres.

[0012] In an embodiment of the present invention, since the pressure-sensitive adhesive layer can exhibit stress transmission even when it is thick, a pressure-sensitive adhesive layer that contains heat-expandable microspheres and has excellent surface smoothness (smoothness before the heat-expandable microspheres are foamed) can be formed. By forming a pressure-sensitive adhesive layer with excellent surface smoothness, a pressure-sensitive adhesive sheet with excellent adhesion to an adherend can be obtained. In addition, a pressure-sensitive adhesive sheet that can hold a semiconductor chip obtained by cleaving with good positional accuracy can be provided. The above effect becomes more advantageous as the semiconductor chip becomes smaller.

[0013] The adhesive strength at 23°C when the adhesive layer of the pressure-sensitive adhesive sheet is attached to polyethylene terephthalate is preferably 0.3 N / 20 mm or more, more preferably 0.5 N / 20 mm to 30 N / 20 mm, even more preferably 0.5 N / 20 mm to 20 N / 20 mm, and even more preferably 3.5 N / 20 mm to 15 N / mm. Within such ranges, for example, a pressure-sensitive adhesive sheet useful as a temporary fixing sheet used in the manufacture of electronic components can be obtained. In this specification, the adhesive strength refers to the adhesive strength in a state where there is no decrease in adhesive strength due to the expansion of the heat-expandable microspheres, and means the adhesive strength in a state where there is no thermal history of 40°C or more. In addition, the adhesive strength refers to the adhesive strength measured by a method in accordance with JIS Z 0237:2009 (lamination conditions: 1 round trip with a 2 kg roller, peel speed (pulling speed): 300 mm / min, peel angle 180°).

[0014] The adhesive strength of the adhesive layer of the pressure-sensitive adhesive sheet when applied to polyethylene terephthalate is preferably reduced by heating to 0.3 N / 20 mm or less (preferably 0.2 N / 20 mm or less, more preferably 0.1 N / 20 mm or less). The heating temperature is preferably 150°C to 300°C, more preferably 170°C to 280°C.

[0015] The thickness of the pressure-sensitive adhesive sheet is preferably 10 μm to 400 μm, more preferably 20 μm to 200 μm, and even more preferably 30 μm to 150 μm.

[0016] The storage modulus E' of the pressure-sensitive adhesive sheet at -15°C is preferably 200 MPa or more and 500 MPa or less. In this range, tearing of the dicing tape can be suppressed, and the die bond sheet can be cut well. The storage modulus E' of the dicing tape at -15°C is preferably 200 MPa or more, and more preferably 220 MPa or more. By increasing the storage modulus E' at -15°C, the die bond sheet can be cut well. That is, better cuttability can be exhibited. The storage modulus E' at -15°C may be 500 MPa or less, or may be 400 MPa or less. By decreasing the storage modulus, tearing of the dicing tape can be suppressed. The storage modulus E' can be measured using a dynamic viscoelasticity measuring device (for example, the product name "RSA-G2" manufactured by TA instruments) under the measurement conditions of a frequency of 1 Hz and a temperature rise rate of 5°C / min.

[0017] B.Resin layer The content of the base polymer in the resin layer is preferably 60% by weight or more, more preferably 70% by weight to 99% by weight, and even more preferably 80% by weight to 99% by weight.

[0018] As described above, the resin layer is formed from a base polymer having a glass transition temperature Tg of -35°C to 20°C. The glass transition temperature of the base polymer constituting the resin layer is preferably -33°C to 18°C, more preferably -30°C to 15°C, even more preferably -25°C to 13°C, more preferably -20°C to 10°C, and particularly preferably -15°C to 10°C. Within such a range, the above-mentioned effects are remarkable. Furthermore, if the glass transition temperature Tg of the base polymer is too low, deformation during heating (for example, heating by laser light irradiation) is large, which may lead to positional displacement of the adherend. Furthermore, if the glass transition temperature Tg of the base polymer is too high, it may be easily broken during the expanding process.

[0019] The glass transition temperature is calculated by the Fox formula. The Fox formula is calculated by dividing the glass transition temperature Tg (℃) of the copolymer by the glass transition temperature Tg (℃) of the homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. i In the Fox formula below, Tg (℃) is the glass transition temperature of the copolymer, W i is the weight fraction of monomer i, Tg i (°C) indicates the glass transition temperature of the homopolymer formed from monomer i. 1 / (273+Tg)=Σ(W i / (273+Tg i )) The glass transition temperature of a homopolymer may be that described in "Polymer Handbook" (4th ed., John Wiley & Sons, Inc., 1999). When multiple Tg values ​​are described in this document, the "conventional" value is used.

[0020] In one embodiment, the base polymer has a structural unit (A1) derived from a monomer (A1) having a glass transition temperature Tg of -20°C to 15°C when made into a homopolymer. The monomer (A1) can be a main monomer constituting the base polymer. The content of the structural unit (A1) is preferably 50 parts by weight or more, more preferably 55 parts by weight or more, based on 100 parts by weight of the base polymer. Within such a range, a pressure-sensitive adhesive sheet having excellent stress transfer properties can be obtained. Furthermore, the content of the structural unit (A1) is, for example, 100 parts by weight or less, based on 100 parts by weight of the base polymer. In one embodiment, the content of the structural unit (A1) is 95 parts by weight or less, based on 100 parts by weight of the base polymer.

[0021] The glass transition temperature Tg of the homopolymer of the monomer (A1) (i.e., the main monomer) is preferably −20° C. to 10° C. If the homopolymer glass transition temperature Tg of the monomer (A1) is less than −20° C., the stress relaxation property may be too high, which may inhibit the expandability of the adherend. If the homopolymer glass transition temperature Tg of the monomer (A1) is more than 15° C., the pressure-sensitive adhesive sheet may break during expansion.

[0022] The base polymer may have a structural unit (B1) derived from a monomer (B1) having a glass transition temperature Tg of 100° C. to 175° C. when made into a homopolymer. The content of the structural unit (B1) is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, and even more preferably 30 parts by weight or less, based on 100 parts by weight of the base polymer. If it is within this range, it is possible to obtain a pressure-sensitive adhesive sheet that is difficult to break when expanded. The content of the structural unit (B1) is preferably 5 parts by weight or more, based on 100 parts by weight of the base polymer. If it is within this range, it is possible to obtain a pressure-sensitive adhesive sheet that is excellent in stress transmission. Note that if a monomer having a glass transition temperature Tg of more than 175° C. when made into a homopolymer is used, there is a risk that the pressure-sensitive adhesive sheet will break when expanded.

[0023] Examples of the monomer (B1) include methyl methacrylate, N-acryloylmorpholine, N-vinyl-2-pyrrolidone, and N-phenylmaleimide. By using these monomers, it is possible to obtain a pressure-sensitive adhesive sheet with excellent stress transmission properties. These monomers may be used alone or in combination of two or more.

[0024] As the base polymer contained in the resin layer, any suitable polymer can be used as long as the effect of the present invention can be obtained. In one embodiment, an acrylic polymer (homopolymer or copolymer) is used as the base polymer contained in the resin layer. The acrylic polymer can be obtained by using one or more (meth)acrylic acid alkyl esters as a monomer component.

[0025] Specific examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and ) C1-20 alkyl esters of (meth)acrylic acid such as nonyl acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, preferred are (meth)acrylic acid alkyl esters having a linear or branched alkyl group having 4 to 20 carbon atoms (more preferably 6 to 20, particularly preferably 8 to 18), and more preferably 2-ethylhexyl (meth)acrylate.

[0026] In one embodiment, a (meth)acrylic acid alkyl ester having a glass transition temperature of -20°C to 15°C is used as the (meth)acrylic acid alkyl ester. In the acrylic polymer, the "(meth)acrylic acid alkyl ester having a glass transition temperature of -20°C to 15°C" may correspond to the above-mentioned "monomer (A1)". In this specification, for convenience, the (meth)acrylic acid alkyl ester having a glass transition temperature of -20°C to 15°C is referred to as the "acrylic monomer (A1)".

[0027] Examples of the acrylic monomer (A1) include ethyl acrylate, methyl acrylate, 2-ethylhexyl methacrylate, etc. Among these, ethyl acrylate or methyl acrylate is preferred.

[0028] When the acrylic polymer is a copolymer, the content of the structural unit derived from the acrylic monomer (A1) is preferably 50 parts by weight or more, more preferably 55 parts by weight or more, even more preferably 60 parts by weight or more, and particularly preferably 70 parts by weight or more, based on 100 parts by weight of the base polymer. If it is within such a range, a pressure-sensitive adhesive sheet having excellent stress transfer properties can be obtained. In addition, the content of the structural unit derived from the acrylic monomer (A1) is, for example, 95 parts by weight or less, preferably 90 parts by weight or less, based on 100 parts by weight of the base polymer.

[0029] The glass transition temperature Tg of the homopolymer of the acrylic monomer (A1) (i.e., a monomer contained in an amount of 50 parts by weight or more) is preferably −20° C. to 10° C. If the homopolymer glass transition temperature Tg of the acrylic monomer (A1) is less than −20° C., the stress relaxation property is high, which may inhibit the expandability of the adherend. If the homopolymer glass transition temperature Tg of the acrylic monomer (A1) is more than 15° C., the pressure-sensitive adhesive sheet may break during expansion.

[0030] The acrylic polymer may contain units corresponding to other monomers copolymerizable with the alkyl (meth)acrylate, if necessary, for the purpose of modifying properties such as cohesive strength, heat resistance, and crosslinkability. Examples of such monomers include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itanoic anhydride; hydroxyl group-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl methacrylate; sulfonic acid group-containing monomers such as styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; (N-substituted) amide monomers such as N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; aminoalkyl(meth)acrylate monomers such as aminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and t-butylaminoethyl(meth)acrylate; alkoxyalkyl(meth)acrylate monomers such as methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide;Succinimide monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide; vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinyl carboxylic acid amides, and styrene. vinyl monomers such as α-methylstyrene and N-vinylcaprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acrylate, Monomers having a nitrogen atom-containing ring such as acryloylmorpholine; glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; acrylic ester monomers having a heterocycle, a halogen atom, a silicon atom, or the like, such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, and silicone (meth)acrylate; polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; olefin-based monomers such as isoprene, butadiene, and isobutylene;Examples of the monomer include vinyl ether monomers such as vinyl ether. These monomers may be used alone or in combination of two or more. Among the above, more preferred are carboxyl group-containing monomers (particularly preferably acrylic acid) or hydroxyl group-containing monomers (particularly preferably hydroxyethyl (meth)acrylate). The content of the structural unit derived from the carboxyl group-containing monomer is preferably 0.1% by weight to 15% by weight, more preferably 0.5% by weight to 10% by weight, based on the total structural units constituting the acrylic polymer. The content of the structural unit derived from the hydroxyl group-containing monomer is preferably 0.1% by weight to 20% by weight, more preferably 0.5% by weight to 10% by weight, and particularly preferably 1% by weight to 7% by weight, based on the total structural units constituting the acrylic polymer. In this specification, (meth)acrylic means acrylic and / or methacrylic.

[0031] In one embodiment, the glass transition temperature Tg of the other monomer is 100° C. to 175° C. The content of the structural unit derived from a monomer (also referred to as comonomer (B1)) having a glass transition temperature Tg of 100° C. to 175° C. is 40 parts by weight or less, more preferably 35 parts by weight or less, and even more preferably 30 parts by weight or less, relative to 100 parts by weight of the base polymer. Within this range, a pressure-sensitive adhesive sheet that is difficult to break during expansion can be obtained. The content of the structural unit derived from comonomer (B1) is preferably 5 parts by weight or more, relative to 100 parts by weight of the base polymer. Within this range, a pressure-sensitive adhesive sheet with excellent stress transferability can be obtained.

[0032] The resin layer may be formed from a resin layer forming composition containing the base polymer. The resin layer forming composition may contain any suitable additive as necessary. Examples of the additive include crosslinkers, tackifiers, plasticizers (e.g., trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, etc.), pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc.

[0033] Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, etc. Among these, isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred.

[0034] Specific examples of the isocyanate-based crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate; and isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HX"). The content of the isocyanate-based crosslinking agent is typically 0.1 to 20 parts by weight, and more preferably 0.5 to 10 parts by weight, relative to 100 parts by weight of the base polymer.

[0035] Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Tetrad C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1500NP"), ethylene glycol Licor diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., product name "Epolite 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., product name "Epolite 70P"), polyethylene glycol diglycidyl ether (manufactured by Nippon Oil & Fats Co., Ltd., product name "Epiol E-400"), polypropylene glycol diglycidyl ether (manufactured by Nippon Oil & Fats Co., Ltd., product name "Epiol P-200"), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, product name "Denacol" Examples of the epoxy crosslinking agent include glycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name "Denacol EX-611"), glycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name "Denacol EX-314"), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name "Denacol EX-512"), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. The content of the epoxy crosslinking agent is typically 0.01 to 10 parts by weight, and more preferably 0.03 to 5 parts by weight, relative to 100 parts by weight of the base polymer.

[0036] As the tackifier, any appropriate tackifier can be used. As the tackifier, for example, a tackifier resin can be used. Specific examples of the tackifier resin include rosin-based tackifier resins (e.g., unmodified rosin, modified rosin, rosin phenol-based resins, rosin ester-based resins, etc.), terpene-based tackifier resins (e.g., terpene-based resins, terpene phenol-based resins, styrene-modified terpene-based resins, aromatic modified terpene-based resins, hydrogenated terpene-based resins), hydrocarbon-based tackifier resins (e.g., aliphatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aromatic hydrocarbon resins (e.g., styrene-based resins, xylene-based resins, etc.), aliphatic and aromatic petroleum resins, aliphatic and alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone-based resins, coumarone-indene resins, etc.), phenol-based tackifier resins (e.g., alkylphenol-based resins, xylene formaldehyde-based resins, resols, novolacs, etc.), ketone-based tackifier resins, polyamide-based tackifier resins, epoxy-based tackifier resins, elastomer-based tackifier resins, etc. Among them, rosin-based tackifier resins, terpene-based tackifier resins, or hydrocarbon-based tackifier resins (such as styrene-based resins) are preferred. The tackifiers may be used alone or in combination of two or more. The amount of the tackifier added is preferably 5 to 100 parts by weight, more preferably 10 to 50 parts by weight, based on 100 parts by weight of the base polymer.

[0037] In one embodiment, the resin layer does not have active energy ray curability. By forming a resin layer that does not have active energy ray curability, it is possible to achieve both the hardness of the adhesive sheet that is favorable for stress transmission and the breaking elongation that allows the adhesive sheet to be favorably stretched. In this specification, "not having active energy ray curability" means that the change in elastic modulus by nanoindentation method due to active energy ray irradiation is 10% or less.

[0038] The loss modulus E'' of the resin layer at -15°C is preferably 10 MPa to 3000 MPa, more preferably 15 MPa to 2500 MPa, and further preferably 20 MPa to 2400 MPa. Within such a range, a pressure-sensitive adhesive sheet having excellent stress transferability can be obtained. In particular, a pressure-sensitive adhesive sheet having excellent stress transferability and exhibiting favorable expandability in a so-called cool expanding step can be obtained. Furthermore, if the loss modulus E'' at -15°C is too low, deformation during heating (e.g., heating by laser light irradiation) is large, which may lead to displacement of the adherend. Furthermore, if the loss modulus E'' at -15°C is too high, breakage may occur easily during the expanding step. The loss modulus E'' can be measured using a dynamic viscoelasticity measuring device (e.g., TA instruments' product name "RSA-G2") under measurement conditions of a frequency of 1 Hz and a heating rate of 5°C / min.

[0039] The storage modulus E' of the resin layer at -15°C is preferably 10 MPa to 2500 MPa, more preferably 15 MPa to 1500 MPa. Within this range, a pressure-sensitive adhesive sheet with excellent stress transferability can be obtained. In particular, a pressure-sensitive adhesive sheet that has excellent stress transferability and exhibits favorable expandability in the so-called cool expansion process can be obtained. If the storage modulus E' at -15°C is too low, deformation during heating (e.g., heating by laser light irradiation) is large, which may lead to displacement of the adherend. If the storage modulus E' at -15°C is too high, breakage may occur easily during the expansion process. The storage modulus E' can be measured using a dynamic viscoelasticity measuring device (e.g., TA instruments' product name "RSA-G2") under measurement conditions of a frequency of 1 Hz and a heating rate of 5°C / min.

[0040] The indentation hardness of the resin layer at -10°C by the nanoindentation method is preferably 0.05 to 15 MPa, more preferably 0.10 to 15.0 MPa, and even more preferably 0.10 to 12.0 MPa. Within such a range, a pressure-sensitive adhesive sheet with excellent stress transferability can be obtained. The indentation hardness by the nanoindentation method refers to a hardness obtained by continuously measuring the load and indentation depth on the indenter when the indenter is pressed into the sample during loading and unloading, and then obtaining a load-indentation depth curve. In this specification, the indentation hardness by the nanoindentation method refers to a hardness measured using a nanoindenter (e.g., Triboindenter TI-950 manufactured by Hysitron Inc.) by a single indentation method at a predetermined temperature (-10°C) under the following measurement conditions: indenter used: Berkovich (triangular pyramid), indentation speed: 300 nm / sec, pull-out speed: 300 nm / sec, indentation depth: 1300 nm.

[0041] The indentation hardness of the resin layer as measured by a nanoindentation method at −10° C. is preferably smaller than the indentation hardness of the substrate as measured by a nanoindentation method at −10° C. By forming such a resin layer, it is possible to obtain a pressure-sensitive adhesive sheet that is difficult to break and is useful as a temporary fixing material in an expanding process.

[0042] The thickness of the resin layer is preferably 5 μm to 40 μm, more preferably 5 μm to 35 μm, further preferably 10 μm to 30 μm, and particularly preferably 10 μm to 20 μm. Within such a range, a pressure-sensitive adhesive sheet that is excellent in stress transferability and is not easily broken during expansion can be obtained.

[0043] C.Adhesive layer As described above, the pressure-sensitive adhesive layer contains heat-expandable microspheres. The pressure-sensitive adhesive layer may further contain a pressure-sensitive adhesive. In one embodiment, the pressure-sensitive adhesive layer has a photothermal conversion ability. The pressure-sensitive adhesive layer having a photothermal conversion ability may, for example, absorb a laser beam of a predetermined wavelength and generate heat. The heat generation may cause the heat-expandable microspheres to expand and foam. If the peelability is expressed by the laser beam, minute adherends can be selectively peeled off. This effect is particularly remarkable in combination with the ability to form a pressure-sensitive adhesive layer with excellent smoothness. As the laser beam, an IR laser beam, a UV laser beam, or the like is used. Preferably, an IR laser beam is used.

[0044] The arithmetic surface roughness Ra of the pressure-sensitive adhesive layer before the expansion of the heat-expandable microspheres (i.e., before heating) is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. Within such a range, a pressure-sensitive adhesive sheet having excellent adhesion to an adherend can be obtained. Also, a pressure-sensitive adhesive sheet capable of adhering to an adherend with good positional accuracy can be obtained.

[0045] The thickness of the pressure-sensitive adhesive layer is preferably 5 μm to 40 μm, more preferably 7 μm to 35 μm, and even more preferably 20 μm to 35 μm. Within such a range, a pressure-sensitive adhesive sheet containing heat-expandable microspheres and having excellent smoothness, high adhesion, and excellent stress transferability can be obtained.

[0046] The pressure-sensitive adhesive layer preferably has an indentation hardness of less than 100 MPa, more preferably 0.1 MPa to 50 MPa, and even more preferably 0.1 MPa to 10 MPa at 25° C. Within such ranges, a pressure-sensitive adhesive sheet having suitable adhesiveness and expandability can be obtained.

[0047] The optical absorptance of the pressure-sensitive adhesive layer at a wavelength of 900 nm is preferably 25% to 100%, more preferably 30% to 95%, and further preferably 40% to 95%. Within such a range, it is possible to form an adhesive layer having a photothermal conversion ability, which preferably generates heat upon irradiation with IR laser light and has excellent releasability due to the heat-expandable microspheres.

[0048] (Adhesive) Examples of the adhesive constituting the adhesive layer include acrylic adhesives, rubber adhesives, and silicone adhesives. Among them, acrylic adhesives can be preferably used. In addition, an active energy ray curable acrylic adhesive (hereinafter, active energy ray curable adhesive) may be used as the adhesive. Details of the adhesive are described in, for example, JP 2015-168711 A. The description of this publication is incorporated herein by reference.

[0049] In one embodiment, an acrylic adhesive is used as the adhesive. Examples of the acrylic adhesive include an acrylic adhesive having an acrylic polymer (homopolymer or copolymer) using one or more (meth)acrylic acid alkyl esters as a monomer component as a base polymer. The polymer described in the above section B can be used as the base polymer.

[0050] The acrylic adhesive may contain any suitable additives as necessary, such as crosslinkers, tackifiers, plasticizers (e.g., trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, etc.), pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc.

[0051] Examples of the crosslinking agent contained in the acrylic adhesive include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, and peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, and amine-based crosslinking agents. Among them, isocyanate-based crosslinking agents or epoxy-based crosslinking agents are preferable. As the isocyanate-based crosslinking agent contained in the acrylic adhesive, for example, the crosslinking agents listed in section B can be used. The content of the isocyanate-based crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.1 parts by weight to 20 parts by weight, and more preferably 0.5 parts by weight to 10 parts by weight, relative to 100 parts by weight of the base polymer. As the epoxy-based crosslinking agent contained in the acrylic adhesive, for example, the crosslinking agents listed in section B can be used. The content of the epoxy-based crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.01 to 10 parts by weight, and more preferably 0.03 to 5 parts by weight, per 100 parts by weight of the base polymer.

[0052] Any suitable tackifier is used as the tackifier contained in the acrylic adhesive. For example, a tackifier resin is used as the tackifier. Specific examples of the tackifier resin include the tackifier resins listed in the above section B. The amount of the tackifier added is preferably 5 to 100 parts by weight, more preferably 10 to 50 parts by weight, based on 100 parts by weight of the base polymer.

[0053] (Thermally expandable microspheres) The heat-expandable microspheres may be any suitable type of heat-expandable microspheres, so long as they are capable of expanding or foaming upon heating. For example, the heat-expandable microspheres may be microspheres having a substance that easily expands upon heating encapsulated in an elastic shell. Such heat-expandable microspheres may be produced by any suitable method, such as a coacervation method or an interfacial polymerization method.

[0054] Examples of substances that easily expand when heated include low-boiling liquids such as propane, propylene, butene, normal butane, isobutane, isopentane, neopentane, normal pentane, normal hexane, isohexane, heptane, octane, petroleum ether, methane halides, and tetraalkylsilanes; azodicarbonamide that gasifies by thermal decomposition; and the like.

[0055] Examples of materials constituting the shell include polymers composed of nitrile monomers such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethoxyacrylonitrile, and fumaronitrile; carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid; vinylidene chloride; vinyl acetate; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and β-carboxyethyl acrylate; styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; and amide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide. Polymers composed of these monomers may be homopolymers or copolymers. Examples of such copolymers include vinylidene chloride-methyl methacrylate-acrylonitrile copolymer, methyl methacrylate-acrylonitrile-methacrylonitrile copolymer, methyl methacrylate-acrylonitrile copolymer, acrylonitrile-methacrylonitrile-itaconic acid copolymer, and the like.

[0056] The heat-expandable microspheres may be made of an inorganic or organic foaming agent, such as ammonium carbonate, ammonium hydrogen carbonate, sodium hydrogen carbonate, ammonium nitrite, sodium borohydride, and various azides. Examples of organic foaming agents include fluorinated alkane compounds such as trichloromonofluoromethane and dichloromonofluoromethane; azo compounds such as azobisisobutyronitrile, azodicarbonamide and barium azodicarboxylate; hydrazine compounds such as paratoluenesulfonylhydrazide, diphenylsulfone-3,3'-disulfonylhydrazide, 4,4'-oxybis(benzenesulfonylhydrazide) and allylbis(sulfonylhydrazide); semicarbazide compounds such as p-toluylenesulfonylsemicarbazide and 4,4'-oxybis(benzenesulfonylsemicarbazide); triazole compounds such as 5-morpholyl-1,2,3,4-thiatriazole; and N-nitroso compounds such as N,N'-dinitrosopentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosoterephthalamide.

[0057] The particle size of the heat-expandable microspheres before heating is preferably 0.5 μm to 80 μm, more preferably 5 μm to 45 μm, further preferably 10 μm to 20 μm, and particularly preferably 10 μm to 15 μm. Thus, the particle size of the heat-expandable microspheres before heating, expressed in terms of average particle size, is preferably 6 μm to 45 μm, more preferably 15 μm to 35 μm. The particle size and average particle size are values ​​determined by a particle size distribution measurement method using a laser scattering method.

[0058] The heat-expandable microspheres preferably have an appropriate strength so that they do not burst until their volumetric expansion rate reaches at least 5 times, more preferably at least 7 times, and even more preferably at least 10 times. When such heat-expandable microspheres are used, their adhesive strength can be efficiently reduced by heat treatment.

[0059] The expansion initiation temperature of the heat-expandable microspheres is preferably 80° C. to 250° C., more preferably 80° C. to 230° C., even more preferably 80° C. to 200° C., even more preferably 80° C. to 150° C., particularly preferably 80° C. to 120° C., and most preferably 80° C. to 100° C. In this specification, the expansion initiation temperature of the heat-expandable microspheres means the lowest temperature at which the thickness of the adhesive layer (when an undercoat layer is provided, the total thickness of the undercoat layer and the adhesive layer) increases by 5% or more from room temperature. For example, the expansion initiation temperature may correspond to the temperature at which the adhesive strength of the adhesive tape becomes 1.0 N / 20 mm or less and 50% or less of the initial adhesive strength.

[0060] The content of the heat-expandable microspheres in the pressure-sensitive adhesive layer can be appropriately set depending on the desired decrease in adhesive strength, etc. The content of the heat-expandable microspheres is, for example, 1 to 150 parts by weight, preferably 10 to 130 parts by weight, and more preferably 25 to 100 parts by weight, relative to 100 parts by weight of the base polymer forming the pressure-sensitive adhesive layer.

[0061] The heat-expandable microspheres can be produced by any suitable method. In one embodiment, the heat-expandable microspheres are obtained by suspension polymerization. Suspension polymerization is usually carried out by dispersing a monomer (shell-forming material) and an organic solvent in an aqueous dispersion medium containing a dispersant, and polymerizing the monomer in the presence of the organic solvent. A dispersion stabilizer for stabilizing the dispersion may be used. Examples of the dispersion stabilizer in the aqueous dispersion medium include inorganic fine particles such as silica, magnesium hydroxide, calcium phosphate, and aluminum hydroxide. Examples of the dispersion stabilizing assistant include condensation products of diethanolamine and aliphatic dicarboxylic acids, polyvinylpyrrolidone, methylcellulose, polyethylene oxide, polyvinyl alcohol, and various emulsifiers.

[0062] The properties of heat-expandable microspheres, such as particle size and organic solvent content, can be controlled by adjusting the polymerization conditions for the suspension polymerization and the types and amounts of the mixed components. For example, heat-expandable microspheres with a large particle size can be obtained by reducing the amount of dispersant added or slowing the stirring speed during polymerization. Heat-expandable microspheres with a thick shell can be obtained by increasing the amount of monomers added or slowing the stirring speed during polymerization.

[0063] (IR absorber) In one embodiment, the adhesive layer includes an IR absorbent. The adhesive layer including the IR absorbent can exhibit peelability by irradiation with IR laser light. Examples of the IR absorbent include carbon black, cesium tungsten oxide, lanthanum hexaboride, tin-doped indium oxide, antimony-doped tin oxide, cyanine compounds, phthalocyanine compounds, dithiol metal complexes, naphthoquinone compounds, diimmonium compounds, and azo compounds. Examples of the resin that constitutes the resin film include polyimide resins, polyethylene terephthalate resins, polyamide resins, polyether ether ketone resins, polyethylene naphthalate resins, acrylic resins, and epoxy resins. Among these, carbon black is preferred.

[0064] The content of the IR absorbent is preferably 0.1 to 30 parts by weight, and more preferably 0.3 to 25 parts by weight, based on 100 parts by weight of the base polymer.

[0065] D. Base material The substrate may be made of any suitable material. As the substrate, various sheet-like materials such as paper, cloth, nonwoven fabric, metal foil, plastic laminates thereof, and laminates of plastics can be used. Among them, plastic films and plastic sheets (hereinafter referred to as plastic films) are most preferable from the viewpoint of handling and cost. The material of the plastic film can be selected as necessary from the viewpoint of strength, heat resistance, and the like. For example, olefin-based resins having α-olefin as a monomer component such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); polyvinyl chloride (PVC); polyphenylene sulfide (PPS); amide-based resins such as polyamide (nylon) and fully aromatic polyamide (aramid); polyether ether ketone (PEEK), polyimide, polyetherimide, polystyrene, and acrylic resins can be mentioned. These materials can be used alone or in combination of two or more. The plastic film may be any of an unstretched film, a uniaxially oriented film, and a biaxially oriented film. These films may be laminated films consisting of two or more film layers, or from the viewpoint of handling, a film containing a lubricant such as inert particles may be appropriately added.

[0066] In one embodiment, the substrate contains a polyolefin resin, preferably a polypropylene resin. By using a substrate formed from a polyolefin resin, a pressure-sensitive adhesive sheet having excellent expandability and useful as a temporary fixing material in an expanding process can be obtained.

[0067] In one embodiment, a multi-layered (e.g., three-layered) substrate is used, which includes a layer formed from a polyolefin resin (preferably polypropylene) and a layer formed from an ethylene-vinyl acetate copolymer resin. By using such a substrate, a pressure-sensitive adhesive sheet having excellent expandability and useful as a temporary fixing material in an expanding process can be obtained. In addition, by using a multi-layered structure and separating the functions of each layer, it is possible to easily achieve both expandability and heat resistance during thermal foaming.

[0068] The thickness of the substrate is preferably 200 μm or less, more preferably 1 μm to 200 μm, further preferably 5 μm to 200 μm, particularly preferably 10 μm to 200 μm, particularly preferably 20 μm to 200 μm, and most preferably 30 μm to 200 μm. If the thickness is within such a range, the effects of the present invention become prominent. In addition, a substrate having excellent strength, flexibility, suppleness, buckling resistance, etc. can be obtained.

[0069] The elastic modulus of the above-mentioned substrate by nanoindentation at 25° C. is preferably 500 MPa to 5000 MPa, more preferably 500 MPa to 4000 MPa, and further preferably 700 MPa to 4000 MPa. In this specification, the elastic modulus by nanoindentation is the elastic modulus measured by a single indentation method at a predetermined temperature (25° C.) using a nanoindenter (e.g., Triboindenter TI-950 manufactured by Hysitron Inc.) under the measurement conditions of an indentation speed of about 500 nm / sec, an extraction speed of about 500 nm / sec, and an indentation depth of about 3000 nm.

[0070] The breaking strength of the substrate at -15°C is preferably 15N / 10mm to 45N / 10mm, more preferably 20N / 10mm to 40N / 10mm. If it is within such a range, it is possible to obtain a pressure-sensitive adhesive sheet that is difficult to break and is useful as a temporary fixing material in an expanding process. The breaking strength can be measured using a tensile tester (e.g., AUTOGRAPH Thermostatic Chamber, AUTOGRAPH AG-I, manufactured by SHIMADZU CORPORATION) under the conditions of sample size: 10mm x 150mm, chuck distance: 50mm, after holding the sample in a chamber at -15°C for 30 minutes, at a pulling speed: 300mm / min.

[0071] The substrate may be subjected to a surface treatment, such as corona treatment, chromate treatment, ozone exposure, flame exposure, high-voltage shock exposure, ionizing radiation treatment, or coating with a primer.

[0072] E. Manufacturing method of adhesive sheet The pressure-sensitive adhesive sheet can be produced by any suitable method. Examples of the method for producing a pressure-sensitive adhesive sheet include a method of directly coating a resin layer-forming composition on a substrate to form a resin layer, and coating a pressure-sensitive adhesive layer-forming composition (pressure-sensitive adhesive + heat-expandable microspheres) on the resin layer, or a method of coating a pressure-sensitive adhesive layer-forming composition on any suitable substrate to form a coating layer, and transferring the formed coating layer to a substrate / resin layer laminate.

[0073] Examples of the coating method of each of the above compositions include coating methods using a die coater, a comma coater, a gravure coater, etc. As a drying method, heat drying is preferably adopted. For example, drying can be performed by placing the pressure-sensitive adhesive coating layer for a desired time in a dryer equipped with a blower that can forcibly circulate air at a predetermined temperature.

[0074] The drying temperature is preferably 55° C. or higher and lower than 100° C., more preferably 60° C. to 90° C., and further preferably 65° C. to 90° C. The drying time can be any appropriate time. The drying time is, for example, 1 minute to 10 minutes. Within this range, the pressure-sensitive adhesive layer and the like can be formed efficiently.

[0075] F.Applications The pressure-sensitive adhesive sheet can be preferably used as a temporary fixing sheet when processing any appropriate member (for example, electronic components such as semiconductor chips). In one embodiment, a dicing die bond film is provided that is configured by laminating the pressure-sensitive adhesive sheet and a die attachment film. FIG. 2 is a schematic cross-sectional view of a dicing die bond film according to one embodiment of the present invention. The dicing die bond film 200 includes a pressure-sensitive adhesive sheet 100 and a die attachment film 40 disposed on one side of the pressure-sensitive adhesive sheet 100. The die attachment film is an adhesive film that is attached to a semiconductor chip before die bonding during semiconductor chip manufacturing, and can be attached to a chip in a wafer state and divided into individual chips together with the wafer during dicing.

[0076] As the die attachment film, a die attachment film known in the art may be used, and therefore a detailed description of the configuration thereof will be omitted. The die attachment film may function, for example, as an adhesive exhibiting curing properties (for example, thermosetting properties). The die attachment film may contain any appropriate thermosetting resin. Examples of the thermosetting resin include epoxy resin, phenolic resin, amino resin, unsaturated polyester resin, polyurethane resin, silicone resin, and thermosetting polyimide resin. A thermoplastic resin may be used in combination in the die attachment film. Examples of the thermoplastic resin include natural rubber, butyl rubber, isoprene rubber, chloroprene rubber, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, polybutadiene resin, polycarbonate resin, thermoplastic polyimide resin, polyamide resin such as 6-nylon and 6,6-nylon, phenoxy resin, acrylic resin, saturated polyester resin such as PET and PBT, polyamideimide resin, fluororesin, and the like. EXAMPLES

[0077] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" are by weight unless otherwise specified.

[0078] [Production Example 1] Production of Base Polymer A To ethyl acetate, 70 parts by weight of methyl acrylate (MA), 30 parts by weight of 2-ethylhexyl acrylate (2EHA), and 10 parts by weight of acrylic acid (AA) were added, and 0.4 parts by weight of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name: Perbutyl O (registered trademark)) was further added as a polymerization initiator. The mixture was stirred at 80 to 90°C for 12 hours to obtain an ethyl acetate solution of polymer A (glass transition temperature Tg: -13°C) with a solid content concentration of 40%.

[0079] [Production Example 2] Production of Base Polymer B To toluene, 70 parts by weight of ethyl acrylate (EA), 30 parts by weight of 2-ethylhexyl acrylate (2EHA), 10 parts by weight of N-phenylmaleimide (PMI), and 4 parts by weight of 2-hydroxyethyl acrylate (HEA) were added, and 0.2 parts by weight of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name: Perbutyl O (registered trademark)) was further added as a polymerization initiator, and the mixture was stirred at 80 to 90°C for 12 hours to obtain a toluene solution of polymer B (glass transition temperature Tg: -14°C) with a solid content concentration of 40%.

[0080] [Production Example 3] Production of Base Polymer C To ethyl acetate, 70 parts by weight of ethyl acrylate (EA), 30 parts by weight of 2-ethylhexyl acrylate (2EHA), 5 parts by weight of methyl methacrylate (MMA), and 4 parts by weight of 2-hydroxyethyl acrylate (HEA) were added, and 0.4 parts by weight of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name: Perbutyl O (registered trademark)) was further added as a polymerization initiator. The mixture was stirred at 80 to 90°C for 12 hours to obtain an ethyl acetate solution of polymer C (glass transition temperature Tg: -32.5°C) with a solid content concentration of 40%.

[0081] [Production Example 4] Production of Base Polymer D In toluene, 100 parts by weight of 2-ethylhexyl acrylate (2EHA), 25.5 parts by weight of acryloylmorpholine (ACMO), and 18.5 parts by weight of 2-hydroxyethyl acrylate (HEA) were added, and 0.2 parts by weight of azobisisobutyronitrile (AIBN) was used as a thermal polymerization initiator. The concentration of all monomers was adjusted to 60% by weight. A polymerization reaction treatment was carried out in a nitrogen stream at 62°C for 6 hours and then at 75°C for 2 hours to obtain an intermediate of an acrylic copolymer. Next, 22.5 parts by weight of 2-methacryloyloxyethyl isocyanate (MOI) and 0.03% by weight of dibutyltin dilaurate relative to the MOI were added as reaction catalysts to the liquid containing the obtained intermediate of the acrylic copolymer. After that, an addition reaction treatment (urethanization reaction) was carried out in an air stream at 50°C for 12 hours to obtain a toluene solution of polymer D (glass transition temperature Tg: -6°C).

[0082] [Production Example 5] Production of Base Polymer E 64 parts by weight of butyl acrylate (BA), 33 parts by weight of methyl methacrylate (MMA), and 3 parts by weight of 2-hydroxyethyl acrylate (HEA) were added to ethyl acetate, and 0.2 parts by weight of azobisisobutyronitrile was further added as a polymerization initiator. The mixture was stirred at 80 to 90°C for 12 hours to obtain an ethyl acetate solution of polymer E (glass transition temperature Tg: -18°C) with a solid content concentration of 40%.

[0083] [Production Example 6] Production of Base Polymer F 100 parts by weight of 2-ethylhexyl acrylate (2EHA) and 20.0 parts by weight of 2-hydroxyethyl acrylate (HEA) were added to toluene, and 0.2 parts by weight of azobisisobutyronitrile (AIBN) was used as a thermal polymerization initiator. The concentration of all monomers was adjusted to 60% by weight. A polymerization reaction treatment was carried out in a nitrogen stream at 62°C for 6 hours and then at 75°C for 2 hours to obtain an intermediate of an acrylic copolymer. Next, 16.0 parts by weight of 2-methacryloyloxyethyl isocyanate (MOI) and 0.03% by weight of dibutyltin dilaurate relative to the MOI were added as reaction catalysts to the liquid containing the obtained intermediate of the acrylic copolymer. After that, an addition reaction treatment (urethanization reaction) was carried out in an air stream at 50°C for 12 hours to obtain a toluene solution of polymer F (glass transition temperature Tg: -53°C).

[0084] [Production Example 7] Production of Base Material A A two-layer substrate was obtained by co-extrusion molding using a T-die extrusion molding machine. The extrusion temperature was 190°C. The thickness and resin composition of each layer were as follows: ·Layer thickness PP-containing layer 1: 80μm PP-containing layer 2: 16μm PP-containing layer 1: Melting point: 124°C, Tensile modulus (90°C): 24.7 [MPa] Main component: Polypropylene resin 1 Other ingredients: Polymer-type antistatic agent PP-containing layer 2: Melting point: 92°C, Tensile modulus (90°C): 1.92 [MPa] Main component: Polypropylene resin 1 (70 parts by weight) Other components: Ethylene-vinyl acetate copolymer (EVA1) (30 parts by weight) EVA1, melting point: 88℃, tensile modulus (90℃): 1.01[MPa]

[0085] [Example 1] (Preparation of resin layer / substrate laminate) Mixed solution A was prepared by mixing an ethyl acetate solution of polymer A (polymer A: 100 parts by weight), 1.5 parts by weight of an isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "Takenate D-101A"), and 0.05 parts by weight of dioctyltin dilaurate. The mixed solution A was applied to one surface of the substrate A using an applicator so that the thickness after solvent evaporation (drying) would be 5 μm. Thereafter, the solvent was evaporated (dried) at 70° C. for 1 minute using a forced convection hot air drying oven to obtain a resin layer / substrate laminate. (Preparation of MRF38 (liner) / adhesive layer (containing heat-expandable microspheres) laminate) A pressure-sensitive adhesive (mixed solution F) was prepared by mixing a toluene solution of polymer F (polymer F: 100 parts by weight), 1.5 parts by weight of an isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "Takenate D-101A"), 30 parts by weight of thermally expandable microspheres (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., product name "FN-100S", foaming start temperature: 125°C, average particle size: 15 μm), and 0.4 parts by weight of a carbon black dispersion (manufactured by Mikuni Sekkei Co., Ltd., product name "MHI Black #PD-837M"). The above pressure-sensitive adhesive (mixed solution B) was applied to the release-treated surface of a liner (PET film, manufactured by Mitsubishi Plastics, Inc., product name "MRF-38") coated with a silicone-based release agent, so that the thickness after solvent evaporation (drying) would be 30 μm. The solvent was then evaporated (dried) at 65°C for 5 minutes using a forced convection hot air drying oven, yielding an MRF38 (liner) / pressure-sensitive adhesive layer (containing thermally expandable microspheres) laminate. (Preparation of MRF38 (liner) / adhesive layer (containing heat-expandable microspheres) / resin layer / substrate laminate) MRF38 (liner) / adhesive layer (containing heat-expandable microspheres) and a resin layer / substrate laminate were bonded together so that the adhesive layer (containing heat-expandable microspheres) and the resin faced each other, to obtain an adhesive sheet consisting of MRF38 (liner) / adhesive layer (containing heat-expandable microspheres) / resin layer / substrate laminate.

[0086] [Examples 2 to 8, Comparative Example 1] A liner-attached adhesive sheet was obtained in the same manner as in Example 1, except that when forming the adhesive layer, the base polymer shown in Table 1 was used and the amount of carbon black dispersion added and the thickness of each layer were as shown in Table 1.

[0087] [Comparative Example 2] A pressure-sensitive adhesive (mixed solution F) was prepared by mixing a toluene solution of polymer F (polymer F: 100 parts by weight), 1.5 parts by weight of an isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "Takenate D-101A"), 30 parts by weight of thermally expandable microspheres (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., product name "FN-100S", foaming start temperature: 125°C, average particle size: 15 μm), and 0.4 parts by weight of a carbon black dispersion (manufactured by Mikuni Sekkei Co., Ltd., product name "MHI Black #PD-837M"). The above-mentioned adhesive (mixed solution F) was applied to one surface of the substrate A so that the thickness after solvent evaporation (drying) was 30 μm. Thereafter, the solvent was evaporated (dried) at 65° C. for 5 minutes using a forced convection hot air drying oven to obtain an adhesive sheet (adhesive layer / substrate).

[0088] <Evaluation> After the liners were peeled off from the liner-attached pressure-sensitive adhesive sheets obtained in the Examples and Comparative Examples, the pressure-sensitive adhesive sheets were subjected to the following evaluations. The results are shown in Table 1.

[0089] (1) Laser peelability The die attach film and the semiconductor chip were placed in this order on the adhesive layer of the adhesive sheet, and IR laser light (wavelength: 940 nm) was irradiated from the substrate side of the adhesive sheet to evaluate the peelability of the adherend (die attach film / semiconductor chip laminate) from the adhesive layer. If the adherend naturally peeled off after irradiation with IR laser light, it was judged as pass (◯), and if it did not naturally peel off, it was judged as fail (×). Evaluation equipment: L13920-611 laser irradiation diameter 6.4mmφ (manufactured by Hamamatsu Photonics) A11612-K8DD5AR Laser light transmission fiber (Hamamatsu Photonics) A15558-55-80DW Laser irradiation unit 6.4mmφ (Hamamatsu Photonics) Evaluation conditions: Output 50W Irradiation time 50msec (2) Die attach film (DAF) cleavability The die attach film and semiconductor wafer (which had been stealth diced) were placed in that order on the adhesive layer of the adhesive sheet, and an attempt was made to break them under the following conditions: A breaking rate of 90% or more was deemed to be a pass, and a breaking rate of less than 90% or when the film broke was deemed to be a fail. Evaluation equipment: DDS (Disco) Die Attachment Film: Chip size: 4mm x 13mm x 30μmt Tip material: Silicon Evaluation conditions: Ambient temperature 0℃ Cool Expand Push-up Height 10mm Cool expand thrust speed 200mm / sec Heat shrink push-up height Heat shrink hot air temperature 250℃ Heat shrink rotation speed 5° / sec (3) DAF Adhesion [Preparation of Die Bond Film (DAF)] Acrylic polymer (product name "SG-P3", Nagase ChemteX Corporation, glass transition temperature 12°C, containing epoxy groups) 35 parts by mass (solid content), 30 parts by mass (solid content) of acrylic polymer (acrylic resin solution obtained by dissolving a copolymer of ethyl acrylate, butyl methacrylate, and glycidyl methacrylate in methyl ethyl ketone: weight average molecular weight Mw = 70,000 / epoxy equivalent = 444 (g / eq) / glass transition temperature Tg = 11°C), Phenolic resin (product name "MEHC-7851SS", manufactured by Meiwa Kasei Co., Ltd.) 6 parts by weight, Silica filler (product name "SE2050-MCV", manufactured by Admatechs Co., Ltd.) 27 parts by weight, - 2 parts by mass of silane coupling agent (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) The above-mentioned raw materials were each added to a predetermined amount of methyl ethyl ketone and mixed to prepare a bonding composition solution having a total solids concentration of 15 mass %. Next, using the prepared adhesive composition, a die bond sheet having a thickness of 10 μm was produced on a PET release liner in the same manner as above. A strong adhesive tape (manufactured by Nitto Denko Corporation, No. 315) was attached to the die-bonding film surface of the laminate obtained by laminating the adhesive sheet obtained in the Examples or Comparative Examples on the die-bonding film produced above, and the laminate was cut into a size of 100 mm wide and 200 mm long. A tensile tester (manufactured by Shimadzu Corporation, AUTOGRAPH AGX-V) was used for the measurement. The substrate and the adhesive layer were chucked with an upper chuck jig, and a peel test was performed at a speed of 100 mm / min with T-type peeling, and the DAF adhesive strength was measured. The measurement was performed at a temperature of 23°C. (4) Storage modulus E' at -15°C Using a dynamic viscoelasticity measuring device (manufactured by TA instruments under the trade name "RSA-G2"), the storage modulus E' and loss modulus E'' of the resin layer, as well as the storage modulus E' of the adhesive sheet were measured under the measurement conditions of a frequency of 1 Hz, a heating rate of 5°C / min, and a measurement temperature of -15°C. (5) Indentation hardness at -10℃ Using a nanoindenter (Triboindenter TI-950 manufactured by Hysitron Inc.), the indentation hardness of the resin layer at -10°C was measured by the single indentation method under the following measurement conditions: indenter used: Berkovich (triangular pyramid), indentation speed: 300 nm / sec, pull-out speed: 300 nm / sec, indentation depth: 1300 nm. (6) IR absorption rate of adhesive layer The IR (wavelength: 900 nm) absorbance of the adhesive layer was measured using a spectrophotometer, model "SOLID SPEC-3700" manufactured by SHIMADZU Corp. The measurement conditions were: measurement wavelength range 280 nm to 2500 nm, scan speed: medium speed, sampling pitch: 1 nm.

[0090] [Table 1] [Explanation of symbols]

[0091] 10 Base material 20 Resin layer 30 Adhesive layer 40 Die Attach Film 100 Adhesive Sheet 200 Dicing and die bonding film

Claims

1. A substrate, a resin layer, and a pressure-sensitive adhesive layer are provided in this order, the pressure-sensitive adhesive layer contains heat-expandable microspheres, The resin layer includes a base polymer, The glass transition temperature Tg of the base polymer is −35° C. to 20° C. Adhesive sheet.

2. The pressure-sensitive adhesive sheet according to claim 1, wherein the resin layer has a loss modulus E'' at -15°C of 10 MPa to 3000 MPa.

3. The pressure-sensitive adhesive sheet according to claim 1, wherein the resin layer has a storage modulus E' at -15°C of 10 MPa to 2500 MPa.

4. The pressure-sensitive adhesive sheet according to claim 1 , wherein the resin layer is not curable with active energy rays.

5. The pressure-sensitive adhesive sheet according to claim 1, wherein the resin layer has a thickness of 5 μm to 40 μm.

6. the base polymer has a structural unit (A1) derived from a monomer (A1) having a glass transition temperature Tg of −20° C. to 15° C. when made into a homopolymer, The content of the structural unit (A1) is 50 parts by weight or more based on 100 parts by weight of the base polymer. The pressure-sensitive adhesive sheet according to claim 1 .

7. the base polymer is an acrylic polymer, The pressure-sensitive adhesive sheet according to claim 6, wherein the monomer (A1) is ethyl acrylate, methyl acrylate, or 2-ethylhexyl methacrylate.

8. the base polymer has a structural unit (B1) derived from a monomer (B1) having a glass transition temperature Tg of 100° C. to 175° C. when made into a homopolymer, The content of the structural unit (B1) is 40 parts by weight or less based on 100 parts by weight of the base polymer. The pressure-sensitive adhesive sheet according to claim 1 .

9. The pressure-sensitive adhesive sheet according to claim 8, wherein the monomer (B1) is methyl methacrylate, N-acryloylmorpholine, N-vinyl-2-pyrrolidone or N-phenylmaleimide.

10. The pressure-sensitive adhesive sheet according to claim 1, wherein the pressure-sensitive adhesive layer has a thickness of 5 μm to 40 μm.

11. The pressure-sensitive adhesive sheet according to claim 1, wherein the pressure-sensitive adhesive layer has a light absorptivity of 25% to 100% at a wavelength of 900 nm.

12. The pressure-sensitive adhesive sheet according to claim 1 , wherein the substrate comprises a polyolefin resin.

13. 2. The pressure-sensitive adhesive sheet according to claim 1, wherein the substrate comprises a layer formed from a polyolefin resin layer and a layer formed from an ethylene-vinyl acetate copolymer resin.

14. A dicing die-bonding film comprising the pressure-sensitive adhesive sheet according to claim 1 and a die attach film.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive sheet with separator, assembly of optical member and method for assembling the same

    JP2003201452A

Cited By

  • Adhesive tape for wafer processing

    WO2025169926A1

  • Adhesive sheet

    WO2025215897A1